Isothermal phase transition and the transition temperature limitation in the lead-free (1-x)Bi0.5Na0.5TiO3-xBaTiO3 system. (15th January 2016) - Zhang, Dawei; Yao, Yonggang; Fang, Minxia; Luo, Zhengdong; Zhang, Lixue; Li, Linglong; Cui, Jian; Zhou, Zhijian; Bian, Jihong; Ren, Xiaobing; Yang, Yaodong
Abstract: Most ferroelectric transitions occur ultrafast and are time independent. However, here in (1-x) (Bi0.5 Na0.5 )TiO3 -xBaTiO3, we have found a ferroelectric phase transition induced solely by increasing waiting time at certain temperatures (isothermal phase transition). Through cooling, a unique metastable state between a relaxor ferroelectric and a ferroelectric is unveiled, which in essence is initially a short-range ordered glassy state and then can evolve into a long-range ordered ferroelectric state through the isothermal process. It is also found that these isothermal ferroelectric transitions only occur within a specific temperature region with different waiting time needed. These features of isothermal phase transition can be understood by Landau theory analysis with the consideration of random defects as a competition between the thermodynamically favored long-range ordered state and the kinetically frustrated short-range ordered glassy state from random defects. This study offers a precise experimental as well as a phenomenological interpretation on the isothermal ferroelectric transition, which may help to further clarify the intricate structure-property relationship in this important lead-free piezoelectric material and other related systems. Graphical abstract: